2020
DOI: 10.1093/aobpla/plaa050
|View full text |Cite
|
Sign up to set email alerts
|

Wind intensity affects fine root morphological traits with consequences for plant-soil feedback effects

Abstract: Wind influences the development, architecture and morphology of plant roots and may modify subsequent interactions between plants and soil (plant-soil feedbacks – PSFs). However, information on wind effects on fine root-morphology is scarce and the extent to which wind changes plant-soil interactions remains unclear. Therefore, we investigated the effects of two wind intensity levels by manipulating surrounding vegetation height in a grassland PSF field-experiment. We grew four common plant species (two grasse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…The mean SRL also varied with distance gradient from the ditch, but it was only evident in birch. Similar to our result, Werger et al [44] showed that the effect of wind intensity on the fine root morphological traits, such as SRA, SRL, and RTD, was uniform in all grassland species. However, our results contradict previously reported species-specific root morphological responses to adverse soil conditions [23,45].…”
Section: Absorptive Root Morphological Variation Along With the Distance From The Ditchsupporting
confidence: 92%
“…The mean SRL also varied with distance gradient from the ditch, but it was only evident in birch. Similar to our result, Werger et al [44] showed that the effect of wind intensity on the fine root morphological traits, such as SRA, SRL, and RTD, was uniform in all grassland species. However, our results contradict previously reported species-specific root morphological responses to adverse soil conditions [23,45].…”
Section: Absorptive Root Morphological Variation Along With the Distance From The Ditchsupporting
confidence: 92%
“…Plant traits can also be driven by environmental factors (Lienin and Kleyer 2012;Milanović et al 2020), thus affecting PSF processes. For example, Werger et al (2020) found wind-induced changes in root morphological traits affected the strength and direction of PSF. Similar to wind, aboveground herbivory was found to influence root morphology, which would most likely affect PSF (Heinze 2020).…”
Section: Plant Functional Traitsmentioning
confidence: 99%
“…Although wind acts and stresses plants aboveground, plant responses appear both directly aboveground and indirectly belowground. For instance, wind effects were found to change morphological traits of shoots such as plant height (Feng et al 2019 ) and leaf morphology (Anten et al 2010 ) aboveground, but also root morphological traits (Werger et al 2020 ) belowground. As abiotic stress, wind and its intensity impacts species of all growth forms, including trees, grasses and forbs, at all life-stages.…”
mentioning
confidence: 99%
“…These results suggest that wind stress by short wind pulses of different intensity promoted the development of thinner roots with increased SRL and SRSA. Besides effects on water and nutrient acquisition (Bardgett et al 2014 ), such changes in root morphology are suggested to increase anchorage (Burylo et al 2009 ; Werger et al 2020 ), as higher root length is assumed to provide better mechanical support (see Zhang et al 2021 ). Furthermore, the decreased RTD under wind action suggests that plants invest less root biomass to obtain given levels of surface area and length and, thus, have greater root–soil contact at less cost (Werger et al 2020 ).…”
mentioning
confidence: 99%